Islam and the Challenge of Civilization: By Abdulwahab Meddeb (translated Jane Kuntz) (New York: Fordham University Press, 2013. 175 pages.) (American Journal of Islam and Society, 2014)
Abdelwahab Meddeb’s Islam and the Challenge of Civilization offers newperspectives on and fresh associations among historical events in a way thatdraws the curtain and adjusts the view among Muslim public intellectuals.Situated within the broad scholarship of Islamic thought, it engages criticallyand creatively with various doctrinal issues that are being manipulated bysome Muslim opinion leaders to support their own bellicose positions. Theauthor reveals the linkages between Islam and other revealed faiths, especiallyduring the former’s “golden age,” which witnessed productive encounters betweentheologians and philosophers of diverse religious orientations.The book comprises six chapters in addition to a prologue, an epilogue,notes, and two appendices. In his prologue, the author argues that “violenceproduced by belief is not unique to Islam but finds virulent expression evenamong beliefs issuing from the Indian subcontinent” (p. viii) and emphasizesthe need for a “check on violence via the return to context” (p. ix). He seeksto awaken Muslims “to the fact that times have changed” (p. x) and that “theworld is a different place” (p. x), which is why “when it comes to religiousidentity” (p. x), Islam cannot continue to “perceive Christianity as if it werestill its medieval antagonist, despite modern notions of nations and peoplesthat have circumscribed the religion” (p. x). The following statement sums upthe author’s thesis: “In short, if Islam is to be cured of its current affliction, itmust get to that post-Islamic, post-religious place where Christianity and Judaismhave managed to arrive” (p. x). This sounds interesting and prompts ameticulous reader to watch out for an elaboration thereof. Unfortunately, suchan elaboration never appears ...